Efficacy and safety of mycophenolate mofetil in patients with IgA nephropathy: an update meta-analysis - Bing Du; Ye Jia; Wenhua Zhou; Xu Min; Lining Miao; Wenpeng Cui (BMC Nephrology, 2017)
Abstract Background The application of mycophenolate mofetil (MMF) in treating patients with immunoglobulin A nephropathy (IgAN) remains uncertain. This update meta-analysis was performed to re-evaluate the therapeutic potential of MMF in IgAN. Methods Articles were obtained by searching the electronic databases without language restriction. Randomized controlled trials studying the role of MMF in treating IgAN were collected. The quality of included studies was critically evaluated. Data analyses were performed by using RevMan 5.3 software. Results A total of 297 articles were screened and eight articles were finally included. Among the eight randomized controlled trials, five and three were high quality and low quality, respectively. Both fixed-effect and random-effect model were used. Pooled results by combining all the eight studies suggested that IgAN patients in MMF group had a higher remission rate than that in control group. Compared to placebo or corticosteroid monotherapy, MMF monotherapy exerted a higher remission rate and side effect rate in both main analysis and subgroup analysis by human race. Compared to corticosteroid plus other immunosuppressive agent therapy, corticosteroid plus MMF therapy had a higher remission rate, lower serum creatinine doubling rate, progression to end-stage renal disease rate and side effects rate. Subgroup analysis by therapeutic regimen further confirmed these results between corticosteroid plus MMF therapy and corticosteroid plus cyclophosphamide therapy. Funnel-plot displayed a symmetrical figure, indicating no publication bias existed. Conclusions MMF has the potential in treatment of IgAN, especially for Asians. The evidence currently available shows that MMF monotherapy has a more efficacy but higher side effects when compared to placebo or corticosteroid monotherapy in treatment of Asians with IgAN. While MMF combined with corticosteroid regimen has a more efficacy and lower side effects when compared with corticosteroid plus cyclophosphamide regimen.